2019
DOI: 10.1029/2019tc005585
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Multiple Thermotectonic Events Accommodated by Crustal‐Scale Faults in Northern Iberia, Spain: Insights From K‐Ar Dating of Clay Gouges

Abstract: Large-scale faults in the continental crust are significant features that control the evolution of sedimentary basins and intraplate mountain chains. Deciphering their evolution is a significant task because faults slip and reactivate in a variety of geological settings. In this work, clay gouges of two major orogen-scale, long-lived faults in northern Iberia, the Río Grío and Vallès-Penedès Faults, were investigated by X-ray diffraction and K-Ar isotopic analysis. Illite polytype determinations of 44 subfract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 88 publications
(112 reference statements)
1
20
0
Order By: Relevance
“…Several studies have suggested that a left-lateral shear zone can be recognized along the Iberian Range and the Basque-Cantabrian rifts system. Geological evidence includes the High Tagus Fault in the Iberian Range (Aldega et al, 2019;Aurell et al, 2019) and the Ventaniella Fault in the Basque-Cantabrian region (e.g., Tavani et al, 2011). The latter fault is often considered in recent reconstructions to accommodate the Iberia-Ebro movement alone (Tugend et al, 2015;Nirrengarten et al, 2018).…”
Section: Strike-slip Structures In the Intra-iberian Basinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that a left-lateral shear zone can be recognized along the Iberian Range and the Basque-Cantabrian rifts system. Geological evidence includes the High Tagus Fault in the Iberian Range (Aldega et al, 2019;Aurell et al, 2019) and the Ventaniella Fault in the Basque-Cantabrian region (e.g., Tavani et al, 2011). The latter fault is often considered in recent reconstructions to accommodate the Iberia-Ebro movement alone (Tugend et al, 2015;Nirrengarten et al, 2018).…”
Section: Strike-slip Structures In the Intra-iberian Basinsmentioning
confidence: 99%
“…It suggests that the transcurrent deformation that results from the eastwards movement of Iberia occurred mainly during the Late Jurassic-Early Cretaceous in northern Iberia along a 100 km scale pull-part or en échelon rift basins formed by the NW-SE-trending Iberian massifs. Indeed, along these massifs, several extensional basins recorded major subsidence and strike-slip deformation during the late-Permian to middle-Cretaceous time interval (Alvaro et al, 1979;Salas et al, 2001;Aldega et al, 2019;Aurell et al, 2019;Soto et al, 2019). However, no geological evidence for lithosphere-scale strike-slip movements has yet been clearly defined in the intra-Iberian basins.…”
Section: Introductionmentioning
confidence: 99%
“…This succession, was inferred to range from earliest Palaeocene to Miocene in age and was grouped into six tectono‐sedimentary units bounded by unconformities associated with successive Alpine compressional events (González & Guimerà, 1993; Simón, 2004). Recently, K‐Ar isotopic dating of illites from clay gouges near the SE front of the Iberian Ranges (Río Grío Fault) provided three groups of absolute ages, for the first time in the study area (Aldega et al, 2019). The Río Grío Fault system was active during Permian‐Triassic and Late Jurassic (Mesozoic rifting phases) and then recorded the compression stages during Campanian (72 Ma) and middle Eocene (43 Ma).…”
Section: The Miravete Salt Anticlinementioning
confidence: 99%
“…Recently, many studies have provided temporal constraints to the fault activity in several fold-and-thrust belts worldwide through different geochronological methods. They include isotopic K-Ar and Ar-Ar dating for cataclasites containing silicate minerals (e.g., [11][12][13]) and U-Th/He, U-Pb dating for the synkinematic carbonate tectonites (e.g., [14,15]). Different authors have applied these methodological approaches also to the study of thrusts in the Apennines (e.g., [16]), and in some cases being able to date multiple reactivations of the thrust faults especially in the case of positive inversion that makes difficult the interpretation of the previous fault kinematics and deformation history (e.g., [17]).…”
Section: Introductionmentioning
confidence: 99%